Rapid collapse and slow structural reorganisation during the refolding of bovine alpha-lactalbumin. - Forge, V; Wijesinha, RT; Balbach, J; Brew, K; Robinson, C; Redfield, C; Dobson, C (1999)
The refolding of bovine alpha-lactalbumin (BLA) from its chemically denatured state in 6 M GuHCl has been investigated by a variety of complementary biophysical approaches. CD experiments indicate that the species formed in the early stages of refolding of the apo-protein have at least 85 % of the alpha-helical content of the native state, and kinetic NMR experiments show that they possess near-native compactness. Hydrogen exchange measurements using mass spectrometry and NMR indicate that persistent structure in these transient species is located predominantly in the alpha-domain of the native protein and is similar to that present in the partially folded A-state formed by the protein at low pH. The extent of the exchange protection is, however, small, and there is no evidence for the existence of well-defined discrete kinetic intermediates of the type populated in the refolding of the structurally homologous c-type lysozymes. Rather, both mass spectrometric and NMR data indicate that the rate-determining transition from the compact partially structured (molten globule) species to the native state is highly cooperative. The data show that folding in the presence of Ca2+ is similar to that in its absence, although the rate is increased by more than two orders of magnitude. Sequential mixing experiments monitored by fluorescence spectroscopy indicate that this slower folding is not the result of the accumulation of kinetically trapped species. Rather, the data are consistent with a model in which binding of Ca2+ stabilizes native-like contacts in the partially folded species and reduces the barriers for the conversion of the protein to its native state. Taken together the results indicate that folding of BLA, in the presence of its four disulphide bonds, corresponds to one of the limiting cases of protein folding in which rapid collapse to a globule with a native-like fold is followed by a search for native-like side-chain contacts that enable efficient conversion to the close packed native structure.